Genome editing systems across yeast species. (December 2020) - Yang, Zhiliang; Blenner, Mark
Abstract : Yeasts are used to produce a myriad of value-added compounds. Engineering yeasts into cost-efficient cell factories is greatly facilitated by the availability of genome editing tools. While traditional engineering techniques such as homologous recombination-based gene knockout and pathway integration continue to be widely used, novel genome editing systems including multiplexed approaches, bacteriophage integrases, CRISPR-Cas systems, and base editors are emerging as more powerful toolsets to accomplish rapid genome scale engineering and phenotype screening. In this review, we summarized the techniques which have been successfully implemented in model yeast Saccharomyces cerevisiae as well as non-conventional yeast species. The mechanisms and applications of various genome engineering systems are discussed and general guidelines to expand genome editing systems from S. cerevisiae to other yeast species are also highlighted.